Strategi Pemberdayaan Ekonomi Masyarakat Melalui Platform E-commerce Lokal - Mukhtar Galib; Muharram Muharram; Arif Mashuri (STIE Jambatan Bulan, 2024)
This research explores community economic empowerment strategies through local e-commerce platforms using a qualitative approach and literature study methods. Data was collected from academic journals, books, annual reports, and news articles to analyze the impacts and challenges of implementing local e-commerce. The research results show that local e-commerce platforms have a significant positive effect in increasing the capacity of SMEs through training, expanding market access, and providing financial and technical support. The increase in income and operational efficiency of SMEs shows the clear benefits of this platform. However, challenges such as limited digital literacy and poor internet connectivity in rural areas hinder optimal implementation. Research recommendations include the need for increased training programs, more intensive technical support, and improvements to internet infrastructure. By overcoming these challenges and implementing effective strategies, local e-commerce platforms can do more to empower the community's economy and encourage sustainable business growth